Nanocarriers escaping from hyperacidified endo/lysosomes in cancer cells allow tumor-targeted intracellular delivery of antibodies to therapeutically inhibit c-MYC. (September 2022) - Chen, Pengwen; Yang, Wenqian; Hong, Taehun; Miyazaki, Takuya; Dirisala, Anjaneyulu; Kataoka, Kazunori; Cabral, Horacio
Abstract: Intracellular protein delivery is a powerful strategy for developing innovative therapeutics. Nanocarriers present great potential to deliver proteins inside cells by promoting cellular uptake and overcoming entrapment and degradation in acidic endo/lysosomal compartments. Thus, because cytosolic access is essential for eliciting the function of proteins, significant efforts have been dedicated to engineering nanocarriers with maximal endosomal escape regardless of the cell type. On the other hand, controlling the ability of nanocarriers to escape from the endo/lysosomal compartments of particular cells may offer the opportunity for enhancing delivery precision. To test this hypothesis, we developed pH-sensitive polymeric nanocarriers with adjustable endosomal escape potency for selectively reaching the cytosol of defined cancer cells with dysregulated endo/lysosomal acidification. By loading antibodies against nuclear pore complex in the nanocarriers, we demonstrated the selective delivery into the cytosol and subsequent nucleus targeting of cancer cells rather than non-cancerous cells both in vitro and in vivo . Systemically injected nanocarriers loading anti-c-MYC antibodies suppressed c-MYC in solid tumors and inhibit tumor growth without side effects, confirming the therapeutic potential of our approach. These results indicated that regulating the ability of nanocarriers to escape from endo/lysosomal compartments in particular cells is a practical approach for gaining delivery specificity.